A contrastive analysis between novice and expert teachers' perceptions of school bilingual programmes / Un análisis comparativo entre las percepciones del profesorado novel y experto sobre los programas escolares bilingües. Issue 4 (1st October 2016) - Durán-Martínez, Ramiro; Beltrán-Llavador, Fernando; Martínez-Abad, Fernando
Abstract: This article aims to report on a contrastive analysis between the perceptions of novice and expert teachers on four key dimensions of implementing CLIL (Content and Language Integrated Learning) in primary and secondary schools in Spain. To this end, we applied a non-experimental research design with an ex-post-facto methodology using questionnaire studies. The instrument employed was an adaptation of a previous questionnaire, which was completed by 151 in-service teachers. From the data analysis, statistically significant differences were obtained in the criteria variables when they concerned the teaching experience in CLIL projects. Our data confirm that expert CLIL teachers prioritize methodological competencies and the ability to integrate language and content over subject knowledge and language proficiency, exhibit a more critical view of published course materials, value cooperation and innovation as integral components of CLIL teaching more highly than novice teachers and are more aware of the benefits of bilingual programmes.